Legitimacy and the Swedish Security Service’s Attempts to Mobilize Muslim Communities - Peterson, Aabby (International Journal of Criminology and Sociology, 2012)
The paper addresses how the Swedish Security Service (SÄPO) is attempting to mobilize the support of the Muslim communities in their counterterrorism strategy, together with their measures to prevent radicalisation processes among Muslim young people. Under what circumstances can we find voluntary cooperation by Muslim Swedes in the state’s anti-terror policing efforts and under what circumstances can we expect that voluntary cooperation will be withheld? The analysis focuses two intertwined factors which I argue influence voluntary cooperation: the potential unintended consequences of the Security Service’s outreach activities and the link between cooperation, institutional legitimacy and procedural justice. It is argued that both the ‘soft’ and ‘hard’ aspects of the Swedish Security Service’s preventive, respective control and intelligence strategies, interconnect to produce unanticipated and unwanted consequences. The Swedish Security Service’s outreach programme can have the unintended consequence that instead of counteracting radicalization processes, the programme, which targets practicing Muslims as per definition potential terrorists, can very well lead to radicalization among young Muslims with experiences of misrecognition.